Climate Change in Indonesian National Online Media Coverage: Agenda Setting and Sentiment Analysis - Tri Hastuti Nur Rochimah; Erwin Rasyid; Muhammad Raqib Mohd Sofian (Komunikator, 2023)
This study aims to analyze how Indonesia’s national online media covers the issue of climate change. Media coverage of climate change is a fairly important issue in Indonesia to analyze how the media makes the issue of climate change a media agenda and, at the same time, monitor how the government’s commitment to the issue of climate change both in terms of policy, prevention, and handling. The method used is a descriptive quantitative content analysis method using a sentiment analysis approach. This study analyzed 3608 titles of news articles published in five Indonesian national online media, namely Antaranews, Detik.com, and Republika.co, Tempo.co, and Tribunnews.com during the five years 2019-2023. The study results show that the frequency of the coverage of climate change issues is most widely reported by Antaranews at 51% and is dominated by positive sentiments as a media company owned by the Indonesian government. In contrast to non-government-owned media, namely Detik.com, Republika, Tempo.co, and Tribunnews.com, the issue of climate change is also on the media agenda, although more than Antara news. This media agenda setting is close to the media framing of climate change issue policies, not merely the amount of coverage but climate change is highlighted on the focus of how weak the handling of the impacts of climate change is.